The Utility of Point-of-Care Testing at Emergency Department Triage by Nurses in Simulated Scenarios. (April 2017) - Pines, Jesse M.; Zocchi, Mark S.; Buchanan, Mary Elizabeth; Shah, Manish N.; Travers, Debbie
Abstract : We developed and tested simulated patient scenarios to assess how normal or abnormal point-of-care (POC) test results at triage change prioritization decisions. This was a cross-sectional study where our team developed simulated scenarios and presented them to triage nurses from 3 academic medical centers. Twenty-four scenarios were constructed on the basis of 12 clinical indications from a protocol previously developed by our team. In each scenario, nurses were presented with 2 patients with the same Emergency Severity Index Version 4 (ESI v.4; Agency for Healthcare Research and Quality, Rockville, MD) triage level (Level 2 or Level 3). One of the patients met the inclusion criteria for POC testing under the protocol (cases), whereas the other patient did not (controls). Nurses were asked which of the 2 patients to prioritize first in 3 separate rounds: first without any POC test results, once with abnormal POC test results for case patients, and once with normal POC test results for case patients. Prioritization decisions that changed on the basis of abnormal POC results were defined as "up-triage" and prioritization decisions that changed on the basis of normal results were defined as "down-triage." A total of 39 nurses completed 468 scenarios. In scenarios without any POC test results, 42.3% of case patients were prioritized first. When POC test results were abnormal, 71.6% of cases were prioritized first. When POC test results were normal, 32.7% of case patients were prioritized first. An abnormal POC test resulted in up-triage in 32.5% of the scenarios. When POC test results were normal, there was down-triage in 18.6% of the scenarios. Up- and down-triage rates varied considerably by scenario and clinical indication. Point-of-care testing at emergency department triage results in reasonably high rates of up- and down-triage in simulated scenarios; however, POC tests for specific indications appear to be more useful than others. Abstract : Supplemental Digital Content is Available in the Text.